2016
DOI: 10.1007/s00262-016-1929-z
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells: a new player in the tumor microenvironment

Abstract: Cancerous cells must cooperate with the surrounding stroma and non-malignant cells within the microenvironment to support the growth and invasion of the tumor. The nervous system is a component of every organ system of the body, and therefore, is invariably at the front line of the tumor invasion. Due to the complexity of the nervous system physiology, this review separately discusses the contributions of the central and peripheral nervous systems to the tumorigenesis and tumor progression. We further focus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 125 publications
0
38
0
Order By: Relevance
“…b-adrenergic blockade is being tested as a treatment option for several malignancies (39). In comparison, little attention has been directed at the peripheral neuroglia as a potential modulator of cancer (11). Myelinating and nonmyelinating SCs comprise the majority of the peripheral glia and are present in almost every anatomic site in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b-adrenergic blockade is being tested as a treatment option for several malignancies (39). In comparison, little attention has been directed at the peripheral neuroglia as a potential modulator of cancer (11). Myelinating and nonmyelinating SCs comprise the majority of the peripheral glia and are present in almost every anatomic site in the body.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of investigations into the neuronal regulation of cancer has increased in recent years, the involvement of the peripheral neuroglia in cancer progression remains poorly understood (11,12). Schwann cells (SC) comprise the majority of the neuroglia of the PNS and are intimately associated with the nerve fibers, providing trophic support and a signaling scaffold for the axon (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we reported that the purified murine DRG neurons can be activated by melanoma cells and, in turn, augment melanoma growth in vivo (17). Understanding that the in vivo microenvironment of peripheral nerves is created and maintained by the nerve ensheathing Schwann cells (SC), the principal glia of the PNS (18), we provided theoretical evidence that SC may aid tumor growth by promoting tumor-favorable conditions through their interaction with malignant cells and the facilitation of the immunosuppressive microenvironment (19). Although the main function of SC is to maintain the integrity of axons, SCs have been shown to increase the integrin-dependent tumor invasion on laminin in the pancreatic and the prostate cancer microenvironment (20).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal fibers could interact with immune cells in the microenvironment and in a multitude of cases these interactions could be immunosuppressive and anti‐inflammatory . Recently, Keskinov et al .…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal fibers could interact with immune cells in the microenvironment and in a multitude of cases these interactions could be immunosuppressive and anti-inflammatory. 38,39 Recently, Keskinov et al found that sensory neurons induced the formation of immunosuppressive microenvironment via attraction of MDSCs in melanoma. 40 FoxP3 + T cell is another type of immune regulatory cell that functions like MDSCs in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%